Analytical and Theoretical Perspectives on Sport-Related VR Research: Spatial Presence Manipulation Guidelines - Jihoon Kim (Journal of Applied Sports Management, 2022)
As more scholars incorporate VR into their research, theoretical frameworks for empirical investigation and methodological guidelines for manipulation become more crucial. Because VR is a relatively new instrument and validating the implementation of VR can be challenging, scholars need to exercise caution when manipulating stimuli and measuring experimental conditions. Thus, the aim of the current essay is twofold: (a) address various methodological challenges (e.g., manipulation check) in recent VR studies and (b) discuss potential theoretical frameworks for future VR research in sport.
Keywords: virtual reality; sport research; metaverse